AB0579 Abatacept in rheumatoid arthritis: Clinical and imaging considerations. (23rd January 2014) - Markatseli, T.E.; Kosta, P.; Saougou, I.; Voulgari, P.V.; Argyropoulou, M.I.; Drosos, A.A.
Abstract : Objectives: To investigate the efficacy and safety of abatacept in patients with rheumatoid arthritis (RA) and to describe abatacept survival rates and reasons for discontinuation. Additionally, to investigate the effectiveness of abatacept on structural damage progression using magnetic resonance imaging (MRI). Methods: Twenty-six patients with established RA (disease duration 18.5±10.8 years) treated with abatacept were included in this prospective, open label study. The majority of the patients (84.6%) were refractory to at least two disease modifying anti-rheumatic drugs (DMARDs), while 17 of the 26 patients (65.4%) were also refractory to at least one biologic agent. Abatacept was given intravenously at weeks 0, 2, 4 and every 4 weeks thereafter for a maximum period of 36 months. Data concerning abatacept efficacy, tolerability, adverse events and drug discontinuation, were recorded. Clinical improvement according to the American College of Rheumatology (ACR) 20% and 50% were recorded. Disease activity for 28 joints (DAS-28) was also measured. Standard methods of survival analysis (Kaplan–Meier)were used, in which abatacept termination due to side effects, lack of efficacy or comorbidity was taken as the end point. All patients had their last follow up by November 2011. MRI scans of the dominant hand were obtained from 10 RA patients before the initiation of abatacept treatment (baseline) and after one year of therapy. The MRI scans were scored by a radiologist with musculoskeletal expertise according to the OMERACT score. The scorer was blinded to clinical data. Results: Twenty-six (100%), 14 (53.8%) and 8 (30.8%) patients completed 12, 24 and 36 months of abatacept therapy respectively. Abatacept therapy resulted in a significant reduction of DAS-28. Additionally, morning stiffness, tender and swollen joint count as well as patients' global assessment decreased significantly after therapy. At 12, 24 and 36 months 23 (88.5%), 13 (92.9%) and 8 (100%) patients achieved the ACR20% criteria for response to treatment, respectively. On the other hand, at 12, 24, 36 months of treatment with abatacept, ACR50% response was achieved by 15 (57.7%), 10 (71.4%) and 6 (75%) patients, respectively. Regarding safety, 10 patients developed infections during follow-up. They were all resolved. Ten patients (38.5%) discontinued abatacept therapy. Among them, 6 discontinued the study due to lack of efficacy, 3 due to adverse drug reactions and one due to comorbidity. According to Kaplan-Meier methods, the "survival rate" of abatacept after the first year of treatment was 100%, after the second year it reached 66.7%, while after 3 years of treatment it was 52.4%. OMERACT score was decreased from 40.1±27.4 at baseline to 28.4±17.1 at 1 year (p=0.043).More specifically, MRI bone edema and MRI synovitis score presented a statistically significant reduction while MRI erosions score remained stable. Conclusions: Abatacept constitute an effective therapeutic option with an acceptable safety profile for patients with RA refractory to conventional therapy with DMARDs and/or to other biologic agents. Abatacept survival rate is high in the first years of treatment. Moreover, abatacept may halt further structural deterioration in RA. Disclosure of Interest: None Declared